Large-size high-performance R-T-B rare earth permanent magnet and preparation method thereof

By optimizing the composition and structure in R-T-B rare earth permanent magnets, combined with dual alloys and grain boundary diffusion technology, the problem of remanent magnets and coercive force improvement in the preparation of large-size high-performance magnets is solved, and the balance of high performance and large-size is achieved.

CN119314769APending Publication Date: 2025-01-14ZHEJIANG INNUOVO MAGNETICS
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411317487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to prepare large-size high-performance R-T-B rare earth permanent magnets, especially in improving the residual magnetism and coercivity of the magnets, and the grain boundary diffusion depth is limited, which cannot meet the performance requirements of large-size magnets.

Method used

By optimizing the components of the magnets along the orientation direction, combining the advantages of dual alloy method and grain boundary diffusion, magnets are prepared by layered powder laying technology. The magnet area A increases coercive force through grain boundary diffusion, and the area B increases coercive force through dual alloy , and by controlling the distribution of heavy rare earth element RH and the alloy of low melting point metal element M2 as auxiliary alloys and diffusion sources, the diffusion depth of RH is promoted and excessive enrichment of heavy rare earth elements in small areas is prevented.

Benefits of technology

The magnet has high residual magnetism (Br≥14.0kGs) and high coercive force (Hcj≥23.0kOe), and the magnet's thickness in the orientation direction can be improved while ensuring high magnetic performance, satisfying large-size high-performance R-T-B rare earths The demand for permanent magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314769A_ABST
    Figure CN119314769A_ABST
Patent Text Reader

Abstract

The invention discloses a large-size high-performance R-T-B rare earth permanent magnet and a preparation method thereof. The thickness of the magnet in the orientation direction is 4-14 mm; the residual magnetism Br of the large-size high-performance magnet is greater than or equal to 14.0 kGs, and the coercive force Hcj is greater than or equal to 23.0 kOe. When the magnet base body is prepared, a layered powder laying mode is adopted, so that the surface layer of the magnet is made of single alloy easy to diffuse, the core part of the magnet is made of double alloy, it is guaranteed that the core part of the magnet has high coercive force, meanwhile, the grain boundary diffusion capacity of the surface layer of the magnet is optimized, and the advantages of the double alloy and grain boundary diffusion are fully combined. Besides, an alloy of a low-melting-point metal element M2 and a heavy rare earth element RH in a certain proportion is adopted as an auxiliary alloy and a grain boundary diffusion source, the diffusion depth of the heavy rare earth element RH is promoted, excessive enrichment of the heavy rare earth element RH in a small area is prevented, and generation of body diffusion is inhibited. According to the method, the coercive force of the magnet is remarkably improved, meanwhile, it is guaranteed that the magnet has high residual magnetism, and the large-size high-performance R-T-B rare earth permanent magnet is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a large-size high-performance RTB rare earth permanent magnet and a preparation method thereof, and belongs to the field of rare earth magnets. Background Art

[0002] With the popularization and application of RTB magnets in various devices, the market demand for large-sized RTB magnets with high magnetic properties is gradually increasing. Grain boundary diffusion is a common method for preparing high-performance RTB rare earth permanent magnets, but due to the limited depth of grain boundary diffusion, it is impossible to prepare magnets with larger sizes in the orientation direction of the magnets by using grain boundary diffusion, and it is difficult to improve the magnetic performance of large-sized magnets. At present, the preparation of large-sized, high-performance RTB rare earth permanent magnets is still a difficult problem in the industry.

[0003] The large-size high-performance magnet described in the present invention refers to a magnet with a remanence Br≥14.0 kGs, a coercive force Hcj≥23.0 kOe, and a thickness in the orientation direction of 4 mm to 14 mm, preferably 10 to 14 mm.

[0004] CN 114334415 A discloses a multilayer grain boundary diffusion method for NdFeB thick magnets, which is achieved by laying the order of diffusant powder-NdFeB magnetic powder-diffusant powder in layers in a mold in 5 to 13 layers, and the number of layers is an odd number, and then sintering and molding in a vacuum environment or nitrogen or inert gas atmosphere to achieve grain boundary diffusion. Although this method can achieve the preparation of high coercive force thick magnets, when using this method, the NdFeB magnetic powder layer adjacent to the diffusant powder layer is very easy to over-diffuse, resulting in a decrease in the remanence of the magnet. It can be seen from the embodiments of the invention that the remanence Br of the magnet prepared by this method is less than 13kGs, which is at a relatively low level.

[0005] The combination of dual alloy and grain boundary diffusion is expected to realize the preparation of large-sized high-performance RTB rare earth permanent magnets. However, in actual production, it is found that although high coercive force magnets can be obtained by directly performing grain boundary diffusion treatment on the matrix prepared by the dual alloy method, the reduction of the remanence of the magnet after diffusion is large, and the thickness of the magnet along the orientation direction is small, which cannot meet the performance requirements of the large-sized high-performance magnets described in the present invention.

[0006] The auxiliary alloys used in the dual alloy method usually include fluorides and oxides of heavy rare earth elements. When this type of compound exists in the grain boundary phase of the magnet, it will hinder the RH diffusion source during the grain boundary diffusion treatment process, thereby resulting in an increase in the reduction of the remanent magnetism of the magnet and insufficient increase in the coercive force. At the same time, the thickness of the magnet along the orientation direction cannot be further increased.

[0007] On the basis of increasing the thickness of the magnet in the orientation direction, how to improve the remanence and coercive force of the magnet to obtain high-performance large-size magnets is a development problem that needs to be solved urgently. Summary of the invention

[0008] In view of the difficulty in preparing large-sized, high-performance RTB rare earth permanent magnets, the present invention combines the advantages of the dual alloy method and grain boundary diffusion by optimizing the composition of the magnet in the vertical space along the orientation direction, and provides a large-sized, high-performance RTB rare earth permanent magnet and a preparation method thereof. The large-sized, high-performance magnet described in the present invention refers to a magnet with a remanence Br ≥ 14.0 kGs, a coercive force Hcj ≥ 23.0 kOe, and a thickness in the orientation direction of the magnet of 4 mm to 14 mm, preferably 10 to 14 mm.

[0009] The technical solution adopted by the present invention is as follows: A large-size, high-performance RTB rare earth permanent magnet, comprising the following components in mass fractions: R: 28.5~31.0wt.%, R includes R1 and RH, RH accounts for 0.1~3.0wt.% of the mass fraction of the magnet, RH is at least one of Dy and Tb; the remainder of R is R1, R1 includes at least one of Nd, Pr, Ho, Gd, Er, Y, La, Ce. In order to ensure that the magnet has a high remanence, the rare earth content of the magnet needs to be controlled to not exceed 31.0wt.% of the mass fraction of the magnet in the present invention; RH accounting for 0.1~1% of the mass fraction of the magnet is obtained by grain boundary diffusion; M1: 0.1~1.0wt.%, M1 is one or more of Zn, W, Mo, V, Mn, Zr, Ti, Nb; M2: 0.1~3.0wt.%, M2 is one or more of Cu, Ga, Al; M2 accounting for 0.01~1% of the mass fraction of the magnet is obtained by grain boundary diffusion; B: 0.85~1.1wt.%, B is boron element.

[0010] The balance is T and other inevitable impurities, and T is Fe or Fe and Co.

[0011] Cu, Ga, and Al elements play an important role in improving the coercivity of the magnet matrix and the subsequent grain boundary diffusion effect, so a certain amount of Cu, Ga, or Al elements must be added in the present invention. Although the Al element can significantly improve the coercivity of the magnet, it has a very obvious effect on reducing the remanence of the magnet. Therefore, when M2 contains Al, the content of the Al element is ≤0.3wt.%; and T contains Fe and Co.

[0012] The addition of Al element will reduce the high temperature magnetic properties of the magnet, and Co element is needed to compensate for the high temperature performance of the magnet. Therefore, in the present invention, when Al is used in M2, a certain content of Co element must also be added.

[0013] Alternatively, M2 is preferably one or both of Cu and Ga.

[0014] The thickness of the magnet in the orientation direction is 4 mm to 14 mm, preferably 10 to 14 mm.

[0015] The large-sized high-performance magnet has a remanence Br≥14.0 kGs and a coercive force Hcj≥23.0 kOe.

[0016] The magnet can be divided into three regions, region A, region B and region A, in the orientation direction, and the thickness X1 of the magnet region A and the thickness X2 of the region B satisfy the following relationship: X2 = (1-15)X1. That is, in the present invention, the thickness X2 of the magnet region B ≥ the thickness X1 of the magnet region A, and X2 is no more than 15 times X1. Preferably, X2 = (2-5)X1.

[0017] The three regions, region A, region B and region A, all contain 2:14:1 main phase particles with heavy rare earth element rich RH shells, and the number of 2:14:1 main phase grains with heavy rare earth element rich RH shells in region A accounts for no less than 40% of the total main phase grains in region A.

[0018] In the present invention, the magnet region A mainly improves the coercive force by grain boundary diffusion, while the region B improves the coercive force of the magnet by a dual alloy. Therefore, all three regions contain 2:14:1 main phase particles with a heavy rare earth element RH shell, and the number of 2:14:1 main phase grains with a heavy rare earth element RH shell in region A accounts for no less than 40% of the total main phase grains in region A. Region B does not form a clear and continuous heavy rare earth element RH shell structure similar to the main phase grains in region A, but forms a discontinuous RH-rich region on the surface of the main phase grains through the local diffusion of the dual alloy. Therefore, in the present invention, the coercive force of the final magnet region B is slightly lower than that of the magnet region A. However, since the demagnetization field of the magnet region A is the largest, the coercive force of the magnet as a whole can be significantly improved by increasing the coercive force of region A. The thickness of region B ≥ the thickness of region A and the low RH characteristics of region B can also ensure that the magnet as a whole has a higher remanence.

[0019] The magnet has a distance of 20 μm from the outer surface of region A to the interface between region A and region B. As the unit distance from the outer surface of region A increases, the average concentration of the heavy rare earth element RH decreases. In the magnet within the region B, with a distance of 20 μm as a basic unit distance, as the distance from the interface between the region A and the region B increases, the difference in average RH element concentration between each basic unit distance is less than 0.1%.

[0020] In the present invention, since the coercive force of region A and region B is improved in different ways, the distribution of heavy rare earth element RH also has different characteristics. Magnet region A improves the coercive force of the magnet by grain boundary diffusion. Therefore, from the outer surface of region A to the interface between magnet region A and region B, the distance is 20 μm as a basic unit distance. As the unit distance from the outer surface of region A increases, the average concentration of heavy rare earth element RH decreases. Magnet region B uses a double alloy method to improve the coercive force of the magnet. Therefore, the distribution of heavy rare earth element RH in the magnet within region B is relatively uniform. With a distance of 20 μm as a basic unit distance, as the distance from the interface between region A and region B increases, the difference in the average concentration of RH elements between each basic unit distance is less than 0.1%.

[0021] The interface between magnet region A and region B can be a surface or a transition region parallel to the magnet orientation direction and with a thickness of 5 to 10 μm. In the present invention, the thickness of region A and region B is mainly controlled by controlling the powder thickness of different regions during magnet molding. When the powder is spread smoothly at the interface, the interface between region A and region B is a plane. When the powder is spread smoothly at the interface, the interface between region A and region B is a transition region parallel to the magnet orientation direction and with a thickness of 5 to 10 μm. The specific schematic diagram is shown as follows. Figure 1 Therefore, in the present invention, it is necessary to control the flatness of the powder spreading to ensure that the interface thickness between region A and region B meets the requirements of the present invention.

[0022] In order to ensure the remanence of the magnet, the average content of heavy rare earth RH elements in region A is higher than the average content of heavy rare earth RH elements in magnet region B. And in order to facilitate the adjustment of the performance of the magnet and meet different customer requirements, the types of heavy rare earth RH elements in region A and region B in the present invention can be the same or different.

[0023] In addition, impurities such as oxygen and carbon will affect the grain boundary diffusion effect of the magnet, reduce the coercive force increment of the diffused magnet, and increase the reduction of the residual magnetism. Therefore, in the present invention, it is necessary to control the total oxygen and carbon content of the magnet. The total content of oxygen and carbon elements in the magnet of the present invention is less than 1000ppm (mass ratio).

[0024] The large-size, high-performance RTB rare earth permanent magnet of the present invention can be prepared by the following steps: S1: raw materials are taken according to the composition ratio, smelted and spun to prepare two SC sheets respectively, which are recorded as SC-1 and SC-3; the composition ratio of SC-1 and SC-3 can be the same or different, preferably the composition ratio of SC-1 and SC-3 is the same, SC-1 and SC-3 are respectively prepared by hydrogen crushing and air flow milling to prepare RTB rare earth magnetic powders F1 and F3; the composition of magnetic powder F1 and magnetic powder F3 can be the same or different, preferably the composition of magnetic powder F1 and magnetic powder F3 is the same, the surface area average particle size SMD of magnetic powder F1 and magnetic powder F3 is the same or different, preferably the surface area average particle size SMD of magnetic powder F1 and magnetic powder F3 is the same; According to the composition ratio of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC flakes SC-L1, and auxiliary alloy L1 powder is prepared by hydrogen crushing and air flow milling; S2: Preparation of rare earth magnetic powder F2 can be carried out in the following two ways: (a) mixing one of SC-1 and SC-3 with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and preparing rare earth magnetic powder F2 by hydrogen crushing and air flow milling, wherein the weight of the auxiliary alloy SC sheet SC-L1 is 0.1wt.%~10.0wt.% of the weight of the mixed SC sheet SC-2; (b) mixing one of the magnetic powders F1 or F3 with the auxiliary alloy L1 powder to obtain rare earth magnetic powder F2; the mixing ratio of the auxiliary alloy L1 powder in the magnetic powder F2 is 0.1wt.%~10.0wt.% of the mass of the magnetic powder F2; However, method (b) is prone to introduce oxygen and carbon impurities, resulting in a high content of oxygen and carbon impurities in the magnet. Therefore, step S2 is preferably performed in the manner of method (a) to prepare rare earth magnetic powder F2. Preferably, the Al content in the magnetic powders F1, F2 and F3 is less than 0.3 wt.%, or does not contain Al; S3: Use layered powder spreading to sequentially fill magnetic powder F1, magnetic powder F2, and magnetic powder F3 into the molding mold; depending on different molding methods, the following two powder spreading methods can be used: (a) When the pressing direction is parallel to the magnetizing direction: a molding die with a lower punch that can be raised and lowered is used for molding. The lower punch of the mold is first adjusted downward by a certain distance A, and then the magnetic powder F1 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance B, and then the magnetic powder F2 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance C, and then the magnetic powder F3 is evenly filled, and the powder is scraped flat for orientation molding; the thickness B of the F2 magnetic powder is 1 to 15 times the thickness A or C of the F1 or F3 magnetic powder, preferably 2 to 5 times; the thickness of the F1 magnetic powder and the F3 magnetic powder can be the same or different, preferably the thickness of the F1 magnetic powder and the F3 magnetic powder is the same; (b) When the pressing direction is perpendicular to the magnetizing direction: the magnetic powder is filled in a partitioning manner perpendicular to the magnetizing direction, and a powder filling partition is placed in the mold, which divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are A, B and C, respectively. The magnetic powder F2 is filled in the middle sub-cavity, and the magnetic powders F1 and F3 are filled in the two side sub-cavities, and then oriented molding is performed; the width B is preferably 1 to 15 times the width of A or C, preferably 2 to 5 times; the widths of A and C can be the same or different, and preferably the widths of A and C are the same; S4: The magnet matrix is ​​prepared by means of orientation molding, isostatic pressing, vacuum sintering and heat treatment; S5: Clean the surface of the magnet substrate obtained in step S4, deposit a diffusion source L2 containing heavy rare earth element RH on two surfaces of the magnet substrate perpendicular to the orientation direction, and perform grain boundary diffusion treatment; the temperature of grain boundary diffusion is 850-1000°C, the holding time is 6-30h, and the vacuum degree is 9×10 -4 Pa~100Pa; after cooling and tempering, the large-size high-performance RTB rare earth permanent magnet is obtained; The composition ratio of SC-1 and SC-3 may be the same or different. Preferably, the composition ratio of SC-1 and SC-3 is the same. SC-1 and SC-3 each independently include the following components in mass fraction: R: 28.8~31.3wt.%, R includes R1 and RH, RH accounts for less than 2.9wt.% of the mass fraction of the magnet, RH may be absent, RH is at least one of Dy and Tb; the remainder of R is R1, R1 includes at least one of Nd, Pr, Ho, Gd, Er, Y, La, Ce; M1: 0.1~1.0wt.%, M1 is one or more of Zn, W, Mo, V, Mn, Zr, Ti, Nb; M2: 0.01~2.99wt.%, M2 is one or more of Cu, Ga, Al; B: 0.85~1.1wt.%, B is boron element.

[0025] The balance is T and other inevitable impurities, and T includes Fe or Fe and Co.

[0026] When M2 contains Al, the content of Al element is ≤0.3wt.%; and T contains Fe and Co.

[0027] During the preparation of magnets, the jet milling process will cause a certain loss of rare earth elements. In order to ensure the rare earth content of the magnet, the rare earth content in the raw material needs to be increased by 0.1~0.5wt.% (preferably 0.3wt.%) on the basis of the set rare earth content of the magnet to ensure the rare earth content of the final magnet.

[0028] The auxiliary alloy L1 and the diffusion source L2 each independently include the following components in mass fraction: RHL: 70.0~99.5wt.% M2L: 0.05~30.0wt.%, Preferably: RHL: 70.0~99.0wt.% M2L: 1.0~30.0wt.% The ingredients are more preferably: RHL: 80.0~95.0wt.% M2L: 5.0~20.0wt.%.

[0029] RHL is at least one of Dy and Tb; M2L is one or more of Cu, Ga, Al, and Co.

[0030] Specifically, in step S5, the tempering treatment temperature is 400-600° C., the insulation time is 1-10 hours, and after the insulation is completed, it is cooled to below 80° C. to obtain the large-size high-performance RTB rare earth permanent magnet.

[0031] In step S5, the weight increase of the diffusion source L2 is preferably 0.5-1 wt % of the mass fraction of the magnet matrix.

[0032] The auxiliary alloy of the traditional double alloy method usually adopts the compound of heavy rare earth element RH, such as oxide and fluoride of RH. However, the melting point of such compounds is high and the diffusion depth is limited, so it will cause the main phase grains around the compounds to diffuse, reducing the residual magnetism and coercive force increment of the magnet. In addition, when the compound of heavy rare earth element RH exists in the grain boundary phase of the magnet, it will become the enrichment area of ​​impurity elements, affecting the redistribution of the grain boundary phase during the secondary aging process, and reducing the effect of improving the coercive force of the magnet. Therefore, the compound of heavy rare earth element RH is not used as the auxiliary alloy in the present invention.

[0033] The alloy of a certain proportion of low melting point metal element M2 and heavy rare earth element RH has the characteristics of low melting point. When used as auxiliary alloy and diffusion source, the alloy can promote the diffusion depth of heavy rare earth element RH, prevent the excessive enrichment of heavy rare earth element RH in a small area, inhibit the generation of body diffusion, and significantly improve the coercive force of the magnet while ensuring that the magnet has a high remanence. In addition, the alloy of low melting point metal element M2 and heavy rare earth element RH has a lower oxygen and carbon content, ensuring that the magnet grain boundary phase has higher fluidity and improving the redistribution ability of the grain boundary phase during low temperature aging.

[0034] The components of the auxiliary alloy L1 and the diffusion source L2 may be the same or different. Preferably, the components of the auxiliary alloy L1 and the diffusion source L2 are the same.

[0035] Furthermore, in the auxiliary alloy L1 or the diffusion source L2, when M2L contains Al, it must also contain Co.

[0036] Al atoms can replace Fe atoms in the main phase, resulting in a decrease in the remanence of the magnet. Co in the magnet matrix is ​​distributed more evenly in the main phase, so when Al is contained in the diffusion source L2 and the auxiliary alloy L1, Al atoms will still replace Fe on the surface of the main phase grains. Since Co atoms can also replace Fe atoms in the main phase, and a certain amount of Co replaces Fe, the remanence of the magnet will increase. Therefore, in the present invention, when Al exists in the auxiliary alloy L1 and the diffusion source L2, a certain amount of Co needs to be added to the auxiliary alloy L1 and the diffusion source L2, so that Co and Al are in a competitive relationship in the process of replacing Fe atoms, reducing the amount of Al atoms replacing Fe atoms, thereby improving the remanence of the magnet.

[0037] When the content of M2 element in the auxiliary alloy L1 and the diffusion source L2 is lower than the recommended range of the present invention, its effect on promoting the RH diffusion depth is reduced, and the coercive force and remanence of the final magnet are reduced. When the content of M2 element is higher than the recommended range of the present invention, the proportion of heavy rare earth element RH decreases, resulting in a decrease in the incremental coercive force of the magnet, and a high concentration of M2 element enriched in the magnet grain boundary phase will reduce the squareness of the final magnet, so the auxiliary alloy L1 and the diffusion source L2 composition must be within the required range of the present invention. At the same time, the present invention can adjust the composition of the auxiliary alloy L1 and the diffusion source L2 to be the same or different according to the performance requirements of the final product, and has higher flexibility. However, in order to reduce the complexity of the production process, it is preferred that the auxiliary alloy L1 and the heavy rare earth element diffusion source L2 have the same composition.

[0038] In the step S2, it is preferred to prepare the rare earth magnetic powder F2 by mixing the SC sheets and then crushing them, that is, the preferred method (a).

[0039] This is because the magnetic powder has a large specific surface area and is very easy to adsorb gas and impurities. In the process of preparing magnetic powder F2, if the powder mixing method (b) is adopted, oxygen and carbon contamination will inevitably occur.

[0040] Therefore, the present invention preferably adopts the method of mixing SC sheets to prepare the mixed magnetic powder F2. The magnet preparation process does not involve the powder mixing step, thereby reducing the risk of the magnet being contaminated by oxygen and carbon impurities, thereby achieving the control of the total content of oxygen and carbon elements in the magnet to be less than 1000ppm (mass ratio).

[0041] During grain boundary diffusion, the diffusion source L2 is prepared and deposited onto the surface of the magnet substrate by one of the following methods, depending on the different covering deposition methods of the diffusion source: B1: melting and casting a large ingot of the raw materials of the diffusion source L2 with a specific ratio, and depositing it on the surface of the magnet substrate by PVD; B2: The raw materials of the diffusion source L2 with a specific ratio are melted, spun and prepared into alloy powder, which is then deposited on the surface of the magnet substrate by powder coating, spraying, printing and the like.

[0042] It is preferred to use the B1 method PVD to deposit on the surface of the magnet substrate. In the B2 method, when the diffusion source L2 is prepared into powder, it is easy to adsorb gas and impurities, and after grain boundary diffusion, it is easy to increase the oxygen and carbon impurity content of the magnet. Using the PVD direct deposition method can reduce oxygen and carbon pollution.

[0043] The diffusion ability of a single alloy matrix is ​​stronger than that of a dual alloy matrix. When preparing a matrix magnet, the present invention uses a single alloy matrix in the diffusion area of ​​the magnet surface, and a dual alloy matrix is ​​used inside the magnet. The spatial component distribution of the above-mentioned magnet along the orientation direction is optimized by layered powder spreading. Therefore, for the matrix magnet prepared by step S4, the coercive force of its surface area is lower than that of area B in the core of the magnet. After the grain boundary diffusion of step S5, the surface area of ​​the magnet is transformed into area A having the characteristics described in the present invention, and the coercive force of area A is higher than that of area B in the core of the magnet. Since the demagnetization field of the magnet is the largest at the magnetic pole, the high coercive force characteristics of area A can significantly improve the magnet's anti-demagnetization ability. For area B in the core of the magnet where the grain boundary diffusion depth is difficult to reach, its coercive force is improved by dual alloy.

[0044] The purpose of the present invention is to prepare a large-sized high-performance RTB rare earth permanent magnet, in order to ensure that the thickness D≥10mm along the orientation direction under the condition of high magnetic properties of the magnet as much as possible. The present invention optimizes the traditional dual alloy and grain boundary diffusion source components. An alloy of a heavy rare earth element RH and a low melting point metal element M2 with a certain ratio is used as the main component of the dual alloy and the diffusion source. This type of alloy has the characteristics of a low melting point, effectively improves the diffusion depth of the RH element in the grain boundary diffusion zone and the dual alloy diffusion zone, and avoids its accumulation in the magnet triple grain boundary phase to cause the generation of body diffusion, so it can significantly improve the remanence and coercive force of the final magnet. In addition, compared with the compound of the heavy rare earth element RH, this type of alloy introduces less impurities into the interior of the magnet, which can improve the dual alloy and grain boundary diffusion effects. Finally, the preparation of a magnet with remanence Br≥14.0kGs, coercive force Hcj≥23.0kOe, and thickness D≥10mm in the orientation direction of the magnet is achieved. It is worth noting that the method provided by the present invention can realize the preparation of large-sized and high-performance magnets, and the method provided by the present invention is also applicable to magnets with smaller thickness.

[0045] The beneficial effects of the present invention are: When preparing the magnet matrix, a layered powder spreading method is used to make the surface of the magnet a single alloy that is easy to diffuse, while the core of the magnet is a dual alloy, ensuring that the core of the magnet has a high coercive force while optimizing the grain boundary diffusion ability of the magnet surface, fully combining the advantages of dual alloys and grain boundary diffusion. In addition, a certain ratio of low-melting-point metal element M2 and heavy rare earth element RH alloy is used as an auxiliary alloy and grain boundary diffusion source to promote the diffusion depth of the heavy rare earth element RH, prevent the excessive enrichment of the heavy rare earth element RH in a small area, and inhibit the generation of body diffusion. While significantly improving the coercive force of the magnet, it is ensured that the magnet has a high remanence, thereby obtaining a large-size, high-performance RTB rare earth permanent magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Schematic diagram of the interface and intersection area between area A and area B.

[0047] Figure 2 Schematic diagram of two methods of filling magnetic powder and orientation molding.

[0048] Figure 3 This is the microstructure diagram of the cross section of region A of the magnet in Experiment No. 1.

[0049] Figure 4 (a) and (b) are the changes in RH content in the depth direction of region A and region B of the magnet in Experiment No. 1, respectively.

[0050] Figure 5 This is the microstructure diagram of the cross section of region B of the magnet in Experiment No. 1. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0052] The raw materials are taken according to the composition ratio, melted, and spun to prepare two SC sheets, which are recorded as SC-1 and SC-3; the composition ratio of SC-1 and SC-3 can be the same or different, preferably the composition ratio of SC-1 and SC-3 is the same, SC-1 and SC-3 are prepared by hydrogen crushing and air flow milling to prepare RTB rare earth magnetic powders F1 and F3; the composition of magnetic powder F1 and magnetic powder F3 can be the same or different; According to the composition ratio of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC flakes SC-L1, and auxiliary alloy L1 powder is prepared by hydrogen crushing and air flow milling; The preparation of rare earth magnetic powder F2 can be carried out in the following two ways: (a): Mix one of SC-1 and SC-3 with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and prepare rare earth magnetic powder F2 by hydrogen crushing and air flow milling, wherein the weight of auxiliary alloy SC sheet SC-L1 is 0.1wt.%~10.0wt.% of the weight of mixed SC sheet SC-2; (b) mixing one of the magnetic powders F1 or F3 with the auxiliary alloy L1 powder to obtain rare earth magnetic powder F2; the mixing ratio of the auxiliary alloy L1 powder in the magnetic powder F2 is 0.1wt.%~10.0wt.% of the mass of the magnetic powder F2; The magnetic powder F1, magnetic powder F2 and magnetic powder F3 are filled into the molding mold in turn by layered powder spreading. The following two powder spreading methods can be used according to different molding methods: (a) When the pressing direction is parallel to the magnetizing direction: a molding mold with a lower punch that can be raised and lowered is used for molding. The lower punch of the mold is first adjusted downward by a certain distance A, and then the magnetic powder F1 is evenly filled; after the powder is scraped flat, the lower punch continues to be adjusted downward by a certain distance B, and then the magnetic powder F2 is evenly filled; after the powder is scraped flat, the lower punch continues to be adjusted downward by a certain distance C, and then the magnetic powder F3 is evenly filled. After the powder is scraped flat, orientation molding is performed; (b) When the pressing direction is perpendicular to the magnetizing direction: the magnetic powder is filled in a partitioning manner perpendicular to the magnetizing direction. A powder filling partition is placed in the mold. The partition divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are A, B and C respectively. The middle sub-cavity is filled with magnetic powder F2, and the two sub-cavities on the sides are filled with magnetic powders F1 and F3. Then orientation molding is performed. Figure 2 Schematic diagram of two types of oriented molding.

[0053] Subsequently, the magnet matrix was prepared by means of orientation molding, isostatic pressing, vacuum sintering and heat treatment. After the surface of the magnet matrix was cleaned, the two surfaces of the magnet perpendicular to the orientation direction were covered with the heavy rare earth element RH diffusion source L2, and the grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 850~1000℃, the holding time was 6~30h, and the vacuum degree was 9×10 -4 Pa~100Pa.

[0054] The heavy rare earth element RH diffusion source L2 is prepared and deposited on the magnet surface by the following method: B1: melt and cast a large ingot of raw materials with a specific ratio and deposit it on the magnet surface by PVD; B2: melt and spin the raw materials with a specific ratio to prepare alloy powder, and deposit it on the magnet surface by powder coating, spraying, printing, etc. The B1 method is preferred.

[0055] The magnet after grain boundary diffusion is heat treated at a temperature of 400-600° C. for a holding time of 1-10 hours, and then cooled to below 80° C. to obtain the large-size, high-performance RTB rare earth permanent magnet.

[0056] The surface of the magnet after heat treatment is sandblasted to expose the fresh surface of the magnet. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0057] Embodiment 1: According to the ratio of SC-1 in Table 1, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, which are recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 by hydrogen crushing and air flow milling. According to the ratio of the components of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1. SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling. The weight of auxiliary alloy SC sheet SC-L1 was 0.9wt.% of the weight of mixed SC sheet SC-2. The composition of auxiliary alloy L1 is as follows: Tb: 85.0wt.% Cu: 10.0wt.% Ga: 5.0wt.% The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is perpendicular to the magnetizing direction during molding. Therefore, the magnetic powder is filled according to the following steps: A powder filling partition is placed in the mold, which divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are 3.0 mm, 12.0 mm, and 3.0 mm, respectively. Then, magnetic powder F1, magnetic powder F2, and magnetic powder F1 are filled in the three sub-cavities, respectively. Figure 2 (b) shown.

[0058] In this embodiment, experiment No. 1 adopts the layered powder spreading method provided by the present invention to prepare a magnet by sequentially filling the mold cavity with magnetic powder F1, magnetic powder F2, and magnetic powder F1. Experiment No. 2 adopts the method of filling all three sub-cavities with magnetic powder F1, and experiment No. 3 adopts the method of filling all three sub-cavities with magnetic powder F2.

[0059] Subsequently, the matrix magnet was prepared by oriented molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank, the thickness of the magnet in the orientation direction was 12 mm, and the length and width of the magnet were 30 mm and 10 mm respectively. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and the grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3×10-3 Pa~3×10 -2 Pa. The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the ratio, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.6wt.% of the mass fraction of the magnet. The composition of the grain boundary diffusion source L2 is as follows: Tb: 85.0wt.% Cu: 10.0wt.% Ga: 5.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510° C. for 3.5 hours. After the heat treatment, it is cooled to below 80° C. to obtain the large-sized, high-performance RTB rare earth permanent magnet.

[0060] The magnet surface is sandblasted to expose the fresh surface. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0061] The magnet compositions (mass fraction) of Experiment No. 1 to Experiment No. 3 are shown in Table 1: Table 1 No. Nd Pr B Dy Cu Ga Tb Ti Fe TRE O(ppm) C(ppm) SC-1 22.9 6.88 0.95 0.1 0.1 0.1 0.22 0.12 Bal 30.10 / / 1 22.8 6.72 0.95 0.1 0.18 0.11 0.68 0.12 Bal 30.30 553 352 2 22.6 6.88 0.95 0.1 0.17 0.10 0.62 0.12 Bal 30.20 562 367 3 22.6 7.07 0.95 0.1 0.20 0.12 0.75 0.12 Bal 30.52 603 355 The magnetic properties of the magnet matrix and the diffusion after experiment No. 1 to experiment No. 3 are shown in Table 2: Table 2 No. Matrix Br / kGs Br / kGs after diffusion Matrix Hcj / kOe Hcj / kOe after diffusion 1 14.37 14.23 18.6 25.3 2 14.40 14.27 14.5 20.3 3 14.22 13.85 19.2 25.6 It can be seen from the data in Tables 1 and 2 that when the magnet matrix is ​​completely prepared with magnetic powder F1 (Experiment No. 2), the remanence of the magnet after grain boundary diffusion is 14.27 kGs, while the coercive force is only 20.3 kOe. The purpose of the present invention is to prepare large-sized, high-performance RTB rare earth permanent magnets. In this embodiment, the thickness of the diffused magnet in the orientation direction is 12 mm, which is far more than the common magnets currently on the market. Due to the limitation of the diffusion depth of the grain boundary diffusion itself, the coercive force increment of the thicker magnet by the grain boundary diffusion is small. The coercive force of the magnet matrix of Experiment No. 2 is only 14.5 kOe, and the coercive force increment of the magnet after grain boundary diffusion is 5.8 kOe. This is also the main reason why it is difficult to prepare large-sized, high-performance RTB rare earth permanent magnets.

[0062] Combining dual alloys with grain boundary diffusion is an idea for preparing large-sized, high-performance RTB rare earth permanent magnets. However, when the dual alloy matrix is ​​directly treated with grain boundary diffusion, the remanence loss of the magnet is large. From the data in Table 2, it can be seen that the dual alloy magnet F2 was used for pressing and forming during the preparation of the experimental No. 3 magnet. The remanence loss of the matrix magnet after diffusion was 0.37 kGs, and the coercive force increment was 6.4 kOe. This is because when the magnet is prepared by dual alloy, a higher concentration of heavy rare earth elements RH will exist in the R-rich phase at the grain boundary of the magnet. During the grain boundary diffusion process, the heavy rare earth element RH mainly diffuses by concentration gradient, and the high concentration of RH elements in the grain boundary phase of the dual alloy matrix will reduce the concentration gradient value formed by the diffusion source in the magnet, thereby reducing the diffusion rate of the heavy rare earth diffusion source, resulting in the accumulation of heavy rare earth elements on the coating surface of the magnet diffusion source, inducing the body diffusion of the magnet, and increasing the remanence loss of the magnet. However, since the heavy rare earth element RH in the dual alloy also has a certain grain boundary diffusion effect during the grain boundary diffusion stage, the coercive force increment of the final magnet will be higher than that of Experiment No. 2. However, since the residual magnetism loss after diffusion is too large, the residual magnetism of the magnet obtained by directly performing grain boundary diffusion treatment on the dual alloy matrix is ​​poor, and it is impossible to obtain a large-sized high-performance RTB rare earth permanent magnet that meets the magnetic property requirements of the present invention.

[0063] The magnet of Experiment No. 1 is prepared by the method provided by the present invention, and the magnet matrix is ​​prepared by layered powder spreading. The core of the magnet is a dual alloy with a high coercive force. From the data in Table 2, it can be seen that the matrix coercive force of the magnet of Experiment No. 1 is significantly higher than that of the matrix prepared by the single alloy method (Experiment No. 1), thereby ensuring that the magnet matrix has a high coercive force. The surface layer of the magnet of Experiment No. 1 is a single alloy that is easy to diffuse, which can ensure the diffusion rate of the heavy rare earth diffusion source, avoid the accumulation of heavy rare earth diffusion sources on the surface of the magnet and induce body diffusion, and reduce the residual magnetism loss of the magnet. From the data in Table 2, it can be seen that the loss of Br after the diffusion of the magnet of Experiment No. 1 is 0.14kGs, and the increase in coercive force is 6.7kOe. It can be seen that the increase in coercive force after the diffusion of the magnet of Experiment No. 1 is basically the same as that of Experiment No. 3, but because the surface layer of the magnet of Experiment No. 1 is a single alloy matrix that is easy to diffuse, the residual magnetism loss is significantly reduced. Therefore, the present invention can increase the thickness of the magnet along the orientation direction while ensuring that the magnet has high magnetic properties, thereby preparing large-size and high-performance RTB rare earth permanent magnets.

[0064] In the present invention, the magnet region A and region B of the experiment No. 1 have different ways of improving the coercive force of the magnet, and the distribution of the heavy rare earth element RH also has different characteristics. The magnet region A improves the coercive force of the magnet by grain boundary diffusion. Therefore, from the outer surface of the magnet region A to the interface between the magnet region A and the region B, with a distance of 20 μm as a basic unit distance, as the unit distance from the outer surface of the region A increases, the average concentration of the heavy rare earth element RH decreases. Figure 3 This is the microstructure diagram of the cross section of magnet region A in experiment No. 1. It can be seen that there are main phase grains with heavy rare earth element-rich shells in a certain depth layer near the magnet diffusion source coating surface in magnet region A, and the shells are clear and continuous. SEM statistics show that the number of main phase grains with heavy rare earth element shells in magnet region A accounts for 40.1% of the total number of grains in region A. The heavy rare earth element-rich shells on the surface of the main phase grains of the magnet have a higher anisotropy field, so they can increase the coercive force of the magnet. The characteristics of the grain boundary diffusion process itself also make the heavy rare earth elements in magnet region A have a gradient distribution feature. From the outer surface of magnet region A to the interface between magnet region A and region B, with a distance of 20μm as a basic unit distance, EPMA surface scanning analysis was used to statistically analyze the heavy rare earth element content of the magnet. The results are shown as follows: Figure 4 (a). It can be seen that the content of heavy rare earth elements on the surface coated with the diffusion source of the magnet is the highest. As the unit distance from the outer surface of region A increases, the average concentration of heavy rare earth elements RH decreases. The surface layer of region A of the magnet has a high content of heavy rare earth elements, and the thickness of the shell layer rich in heavy rare earth elements formed on the surface of the main phase grains is relatively large, so the coercive force of the surface layer of region A of the magnet is high. For sintered RTB rare earth permanent magnets, the demagnetization field at the magnetic pole is the largest, so the high coercive force characteristics of this region can ensure that the magnet as a whole has a high coercive force.

[0065] In experiment No.1, magnet region B was prepared by dual alloy, and its cross-sectional microstructure is shown in Figure 5 As shown. It can be seen that the shell structure formed by the main phase grains in the magnet region B is not as uniform as that in region A. Due to the uneven distribution of the dual alloy powder particles, the shell thickness formed on the side of the main phase grains close to the dual alloy particles is larger, while the shell thickness formed on the side away from the dual alloy particles is thinner. And in the present invention, the remanence of the magnet is mainly guaranteed by region B, so the addition ratio of the dual alloy powder is strictly controlled. Therefore, the coercive force of the magnet region B in the present invention is slightly lower than the coercive force of the magnet region A. The experimental No. 1 magnet region A was cut off by diamond wire cutting, and then the magnetic properties of the magnet were tested. The remanence of the magnet is 14.30kGs, and the coercive force is 24.6kOe. In addition, due to the characteristics of the dual alloy preparation process, the distribution of heavy rare earth elements in the magnet region B is more uniform relative to region A. In the magnet region B, with a distance of 20μm as a basic unit distance, EPMA surface scanning analysis is used to statistically analyze the heavy rare earth element content of the magnet. The results are as shown Figure 4 (b) As shown. It can be seen that as the distance from the interface between region A and region B increases, the average concentration of RH elements between each basic unit distance is basically the same, and the concentration difference is less than 0.1%. And by comparison, it can be found that the RH concentration of magnet region A is higher than that of magnet region B.

[0066] The present invention adopts a layered powder spreading method to make the surface layer of the magnet a single alloy that is easy to diffuse, while the core of the magnet is a dual alloy. While ensuring that the core of the magnet has a high coercive force, the grain boundary diffusion capacity of the surface layer of the magnet is optimized, and the advantages of dual alloys and grain boundary diffusion are fully combined. In addition, an alloy of a low-melting-point metal element M2 and a heavy rare earth element RH with a certain ratio is used as an auxiliary alloy and a grain boundary diffusion source to promote the diffusion depth of the heavy rare earth element RH, prevent the excessive enrichment of the heavy rare earth element RH in a small area, and inhibit the generation of body diffusion. While ensuring that the magnet has high remanence and high coercive force, the thickness D along the orientation direction is ≥10mm, thereby preparing a large-size, high-performance RTB rare earth permanent magnet.

[0067] Embodiment 2: According to the ratio of SC-1 in Table 3, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, which are recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 by hydrogen crushing and air flow milling. According to the ratio of the components of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1. The composition of auxiliary alloy L1 is as follows: Tb: 80.0wt.% Cu: 10.0wt.% Ga: 10.0wt.% SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling.

[0068] In this embodiment, experiment No. 4 uses the SC sheet obtained by the above auxiliary alloy L1 composition ratio, experiment No. 5 uses terbium oxide powder as auxiliary alloy L1 powder, and experiment No. 6 uses terbium fluoride powder as auxiliary alloy L1 powder. In experiments No. 5 and 6, the magnetic powder F1 is mixed with the auxiliary alloy L1 powder by mixing powder to obtain rare earth magnetic powder F2 respectively; In experiment No. 4, the weight of the auxiliary alloy SC sheet was 0.65 wt.% of the weight of the mixed SC sheet SC-2; in experiments No. 5 and 6, the mass of the auxiliary alloy L1 powder was 0.65% of the mass of the magnetic powder F2.

[0069] The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is perpendicular to the magnetizing direction during molding. Therefore, the magnetic powder is filled according to the following steps: A powder filling partition is placed in the mold, which divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are 3.0 mm, 12.0 mm, and 3.0 mm, respectively. Then, magnetic powder F1, magnetic powder F2, and magnetic powder F1 are filled in the three sub-cavities, respectively. Figure 2 (b) shown.

[0070] Subsequently, the matrix magnet was prepared by orientation molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank and the thickness of the magnet in the orientation direction was 12 mm. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and the grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3 × 10 -3 Pa~3×10 -2 Pa. The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the ratio, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.8wt.% of the mass fraction of the magnet. The composition of the grain boundary diffusion source L2 is as follows: Tb: 80.0wt.% Cu: 10.0wt.% Ga: 10.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510° C. for 3.5 hours. After the heat treatment, it is cooled to below 80° C. to obtain the large-sized, high-performance RTB rare earth permanent magnet.

[0071] The magnet surface is sandblasted to expose the fresh surface. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0072] The magnet compositions (mass fraction) of Experiment No. 4 to Experiment No. 6 are shown in Table 3: Table 3 No. Nd Pr B Cu Ga Co Tb Zr Fe TRE O(ppm) C(ppm) SC-1 22.45 7.52 0.98 0.12 0.10 0.5 0.17 0.17 Bal 30.14 / / 4 22.3 7.35 0.98 0.20 0.15 0.5 0.65 0.17 Bal 30.30 525 344 5 22.5 6.95 0.98 0.18 0.13 0.5 0.75 0.17 Bal 30.20 1236 682 6 22.6 6.92 0.98 0.18 0.13 0.5 0.74 0.17 Bal 30.26 600 425 The magnetic properties of the magnet matrix and the diffusion after experiment No. 4 to experiment No. 6 are shown in Table 4: Table 4 No. Matrix Br / kGs Br / kGs after diffusion Matrix Hcj / kOe Hcj / kOe after diffusion 4 14.40 14.32 17.6 24.5 5 14.18 13.92 16.3 22.8 6 14.19 13.91 16.6 22.5 In this embodiment, the auxiliary alloys of Experiment No. 4 to 6 respectively use the auxiliary alloy L1, terbium oxide and terbium fluoride provided by the present invention. From the proportion of RH elements in the auxiliary alloys, it can be seen that the mass fraction of terbium in the auxiliary alloy terbium oxide (Tb2O3) of Experiment No. 5 is about 86.9%, and the mass fraction of terbium in the auxiliary alloy terbium fluoride (TbF3) of Experiment No. 6 is 89.3%. Therefore, the proportion of heavy rare earth elements RH in Experiment No. 5 and No. 6 is higher than the Tb content (80%) in Experiment No. 4, but from the magnet properties in Table 4, it can be seen that the remanence and coercive force of the matrix of Experiment No. 4 are higher than those of Experiment No. 5 and Experiment No. 6. In the dual alloy method, the heavy rare earth elements in the auxiliary alloy powder will diffuse to the adjacent main phase grains during the high-temperature sintering stage of the magnet, forming a RH-rich shell on the surface of the main phase grains. The present invention uses an alloy of a low melting point metal element M2 and a heavy rare earth element RH as auxiliary alloy powder, which melts at high temperatures and flows along the grain boundaries. Therefore, after high temperature sintering, the shell formed by the main phase grains is relatively uniform, the coercive force of the magnet is more significantly improved, and the residual magnetism loss is lower.

[0073] Experiment No. 5 and Experiment No. 6 use compounds of heavy rare earth elements with higher melting points as auxiliary alloy powders. The high melting point characteristics make the auxiliary alloy powders unable to melt and flow during the high-temperature sintering stage of the magnet, so the diffusion distance of the heavy rare earth element RH is limited. The main phase grains of the magnet will form a higher shell layer on the side close to the auxiliary alloy powder, while the shell layer formed on the side away from the auxiliary alloy powder is thinner, so the final coercive force of the magnet is not as good as that of Experiment No. 4. In addition, since the shell layer formed on the side close to the auxiliary alloy powder is thicker, the residual magnetism loss of the main phase grains is also larger, resulting in a lower final remanence of the magnet.

[0074] It can also be seen from Tables 3 and 4 that experiments No. 4 to 6 in the present invention all use grain boundary diffusion sources of the same composition for grain boundary diffusion treatment, but the coercive force increase and residual magnetism loss of the magnets after diffusion also have different characteristics. The coercive force increment of the magnet of experiment No. 4 is large after diffusion, and the residual magnetism loss is small. The coercive force increment of the magnets of experiments No. 5 and No. 6 after grain boundary diffusion is relatively low, while the residual magnetism loss is large. By comparing the composition of the magnets of experiments No. 4 to 6, it can be seen that the oxygen and carbon content of the magnet of experiment No. 4 is at a relatively low level, while the oxygen and carbon content of the magnets of experiments No. 5 and No. 6 is relatively high, especially the magnet of experiment No. 5 uses terbium oxide as the auxiliary alloy powder, and the oxygen content of the final magnet is much higher than that of the magnets of the other two experiments.

[0075] The oxygen and carbon in the magnet are mainly present in the R-rich phase at the grain boundary, and will form oxides and carbides in the triple grain boundary phase of the magnet. Grain boundary diffusion and the diffusion of the dual alloy powder both move along the grain boundary phase. When oxides and carbides exist in the magnet grain boundary phase, they will hinder the diffusion of heavy rare earth elements along the grain boundary. Therefore, it eventually leads to an increase in the amount of residual magnetism loss of the magnet after diffusion and a decrease in the coercive force increment. In addition, the oxygen and carbon impurities of the auxiliary alloy powder improved by the present invention are very low, which can effectively reduce the final oxygen and carbon content of the magnet. Therefore, the present invention adopts an alloy of a low melting point element M2 and a heavy rare earth element RH as an auxiliary alloy, and controls the total oxygen and carbon content in the magnet to be less than 1000ppm, thereby ensuring the preparation of large-size and high-performance RTB rare earth permanent magnets.

[0076] Embodiment three: According to the ratio of SC-1 in Table 5, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, which are recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 by hydrogen crushing and air flow milling. According to the ratio of the components of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1. The composition of auxiliary alloy L1 is as follows: Tb: 80.0wt.% Ga: 20.0wt.% SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling. The weight of auxiliary alloy SC sheet SC-L1 was 0.9wt.% of the weight of mixed SC sheet SC-2; The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is parallel to the magnetizing direction during molding, so the magnetic powder is filled according to the following steps: The molding is performed using a molding die with a lower punch that can be raised and lowered. The lower punch of the mold is first adjusted downward by a certain distance A, and then evenly filled with magnetic powder F1; after the powder is scraped flat, the lower punch continues to be adjusted downward by a certain distance B, and then evenly filled with magnetic powder F2; after the powder is scraped flat, the lower punch continues to be adjusted downward by a certain distance C, and then evenly filled with magnetic powder F3. After the powder is scraped flat, orientation molding is performed. In experiment No.7, A, B, and C are 3.6mm, 10.8mm, and 3.6mm, respectively. In experiment No.8, A, B, and C are 7.2mm, 3.6mm, and 7.2mm, respectively. Figure 2 (a) shown.

[0077] Subsequently, the matrix magnet was prepared by orientation molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank and the thickness of the magnet in the orientation direction was 12 mm. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and the grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3 × 10 -3 Pa~3×10 -2 Pa. The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the ratio, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.5wt.% of the mass fraction of the magnet. The composition of the grain boundary diffusion source L2 is as follows: Tb: 80.0wt.% Ga: 20.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510° C. for 3.5 hours. After the heat treatment, it is cooled to below 80° C. to obtain the large-sized, high-performance RTB rare earth permanent magnet.

[0078] The magnet surface is sandblasted to expose the fresh surface. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0079] The thickness ratios of different regions of the magnets were measured. The X2 / X1 ratio of the magnet No. 7 in the experiment was 3, which was within the required range of the present invention. However, the X2 / X1 ratio of the magnet No. 8 in the experiment was 0.5, which was not within the required range of the present invention.

[0080] The magnet compositions (mass fraction) of Experiment No. 7 and Experiment No. 8 are shown in Table 5: Table 5 No. Nd Pr B Cu Dy Ga Tb Zr Fe TRE O(ppm) C(ppm) SC-1 23.57 6.58 0.96 0.18 0.1 0.12 0.12 0.1 Bal 30.37 / / 7 23.6 6.39 0.96 0.18 0.1 0.25 0.61 0.1 Bal 30.70 533 362 8 23.4 6.51 0.96 0.18 0.1 0.18 0.45 0.1 Bal 30.46 585 410 In this embodiment, since the thickness of region B of the Experiment No. 7 magnet is thicker than that of the Experiment No. 8 magnet, that is, the area occupied by the dual alloy in the Experiment No. 7 magnet is larger, the content of the low melting point element M2 and the heavy rare earth element RH is higher than that of the Experiment No. 8 magnet.

[0081] The magnetic properties of the magnet matrix and the diffusion after experiment No. 7 and experiment No. 8 are shown in Table 6: Table 6 No. Matrix Br / kGs Br / kGs after diffusion Matrix Hcj / kOe Hcj / kOe after diffusion 7 14.39 14.28 17.6 25.1 8 14.44 14.34 14.0 21.5 The present invention combines the advantages of dual alloy and grain boundary diffusion by layered powder pressing to prepare large-sized high-performance RTB rare earth permanent magnets. Since grain boundary diffusion has a limitation of small diffusion depth, in the present invention, the region B at the center of the magnet is prepared by dual alloy, and its thickness is within a certain range to ensure the coercive force of the core of the magnet. The region A outside the magnet is prepared by a single alloy to ensure that the surface of the magnet has better diffusion characteristics. Therefore, the thickness X2 of the magnet region B and the thickness X1 of the magnet region A in the present invention need to satisfy X2=(1-15)X1. In this embodiment, X2=3X1 of the experimental No. 7 magnet, and X2=0.5X1 of the experimental No. 8 magnet. The thickness of region B in the center of the experimental No. 8 magnet is relatively low, so although the remanence of the matrix of the experimental No. 8 magnet is higher than that of the experimental No. 7, the coercive force of the matrix is ​​significantly lower than that of the experimental No. 7 magnet. From the data in Table 6, it can be seen that although the coercive force increments of the magnets of Experiment No. 7 and Experiment No. 8 are basically the same after grain boundary diffusion, the coercive force of the final magnet of Experiment No. 8 is at a lower level due to the low coercive force of the magnet matrix. Therefore, in the present invention, in order to prepare large-sized and high-performance RTB rare earth permanent magnets, it is necessary to adjust the thickness X2 of the magnet region B and the thickness X1 of the magnet region A to satisfy X2=(1-15)X1.

[0082] Embodiment 4: According to the ratio of the three SC-1s in Table 7, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 through hydrogen crushing and air flow milling. According to the composition ratio of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1.

[0083] The composition of auxiliary alloy L1 is as follows: Dy: 85.0wt.% Cu: 10.0wt.% Ga: 5.0wt.% SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling. The weight of auxiliary alloy SC sheet SC-L1 was 0.9wt.% of the weight of mixed SC sheet SC-2; In this embodiment, the Al content in the SC-1 composition corresponding to Experiment No. 9 to Experiment No. 11 is different, namely 0, 0.2 wt.% and 0.35 wt.%, respectively. The contents of other elements are the same, as shown in Table 7.

[0084] The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is perpendicular to the magnetizing direction during molding. Therefore, the magnetic powder is filled according to the following steps: A powder filling partition is placed in the mold, which divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are 3.0 mm, 12.0 mm, and 3.0 mm, respectively. Then, magnetic powder F1, magnetic powder F2, and magnetic powder F1 are filled in the three sub-cavities, respectively. Figure 2 (b) shown.

[0085] Subsequently, the matrix magnet was prepared by orientation molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank and the thickness of the magnet in the orientation direction was 12 mm. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3 × 10 -3 Pa~3×10 -2 Pa. The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the ratio, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.6wt.% of the mass fraction of the magnet. The composition of the grain boundary diffusion source L2 is as follows: Dy: 85.0wt.% Cu: 10.0wt.% Ga: 5.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510° C. for 3.5 hours. After the heat treatment, it is cooled to below 80° C. to obtain the large-sized, high-performance RTB rare earth permanent magnet.

[0086] The magnet surface is sandblasted to expose the fresh surface. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0087] The magnet compositions (mass fraction) of Experiment No. 9 to Experiment No. 11 are shown in Table 7: Table 7 No. Nd Pr B Cu Ga Co Dy Ti Al Fe TRE O(ppm) C(ppm) SC-1 (NO.9) 22.75 7.08 0.98 0.08 0.09 1.2 0.20 0.12 0 Bal 30.03 / / SC-1 (NO.10) 22.75 7.08 0.98 0.08 0.09 1.2 0.20 0.12 0.25 Bal 30.03 SC-1 (NO.11) 22.75 7.08 0.98 0.08 0.09 1.2 0.20 0.12 0.35 Bal 30.03 9 22.6 6.83 0.98 0.20 0.12 1.2 0.69 0.12 0 Bal 30.12 532 371 10 22.7 6.78 0.98 0.20 0.12 1.2 0.69 0.12 0.20 Bal 30.17 510 388 11 22.8 6.87 0.98 0.20 0.12 1.2 0.70 0.12 0.35 Bal 30.37 587 315 The magnetic properties of the magnet matrix and the diffusion after experiment No. 9 to experiment No. 11 are shown in Table 8: Table 8 No. Matrix Br / kGs Br / kGs after diffusion Matrix Hcj / kOe Hcj / kOe after diffusion 9 14.40 14.25 18.1 22.6 10 14.23 14.10 18.5 22.8 11 14.09 13.90 19.1 23.3 In this embodiment, no Al is added to the magnet of Experiment No. 9, while 0.20wt.% and 0.35wt.% of Al are added to Experiment No. 10 and Experiment No. 11, respectively. Al can improve the coercive force of the magnet to a certain extent, but it will significantly reduce the remanence of the magnet. Therefore, in order to make the performance of the magnet meet the large-size and high-performance RTB rare earth permanent magnet described in the present invention, the Al content of the magnet in the present invention should be less than 0.3wt.%, and preferably no Al is added to the magnet.

[0088] Embodiment five: According to the ratio of SC-1 in Table 9, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, which are recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 by hydrogen crushing and air flow milling. According to the ratio of the components of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1. The composition of auxiliary alloy L1 is as follows: Tb: 80.0wt.% Cu: 20.0wt.% SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling. The weight of auxiliary alloy SC sheet SC-L1 was 0.9wt.% of the weight of mixed SC sheet SC-2; The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is parallel to the magnetizing direction during molding, so the magnetic powder is filled according to the following steps: The molding process is performed using a molding die with a lower punch that can be raised and lowered. The lower punch of the mold is first adjusted downward by a certain distance A, and then the magnetic powder F1 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance B, and then the magnetic powder F2 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance C, and then the magnetic powder F3 is evenly filled. After the powder is scraped flat, orientation molding is performed. In experiment No. 12, A, B, and C are 3.6 mm, 10.8 mm, and 3.6 mm, respectively. In experiment No. 13, A, B, and C are 2.4 mm, 7.2 mm, and 2.4 mm, respectively. Figure 2 (a) shown.

[0089] Subsequently, the matrix magnet was prepared by oriented molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank. The thickness of the magnet No. 12 in the orientation direction was 12 mm, and the thickness of the magnet No. 13 in the orientation direction was 8 mm. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and the grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3 × 10-3 Pa~3×10 -2 Pa. The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the ratio, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.5wt.% of the mass fraction of the magnet. The composition of the grain boundary diffusion source L2 is as follows: Tb: 80.0wt.% Cu: 20.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510° C. for 3.5 hours. After the heat treatment, it is cooled to below 80° C. to obtain the large-sized, high-performance RTB rare earth permanent magnet.

[0090] The magnet surface is sandblasted to expose the fresh surface. The magnet composition is tested by ICP, and the oxygen and carbon content of the magnet is tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet are analyzed by SEM and EPMA. The magnetic properties of the magnet are tested by NIM-62000 equipment.

[0091] The magnet compositions (mass fraction) of Experiment No. 12 and Experiment No. 13 are shown in Table 9: Table 9 No. Nd Pr B Cu Ga Tb Zr Fe TRE O(ppm) C(ppm) SC-1 23.7 6.59 0.91 0.17 0.25 0.18 0.20 Bal 30.47 / / 12 23.6 6.39 0.91 0.23 0.25 0.61 0.20 Bal 30.60 533 362 13 23.5 6.49 0.91 0.23 0.25 0.61 0.20 Bal 30.60 535 346 The magnetic properties of the magnet matrix and the diffused magnetic properties of Experiment No. 12 and Experiment No. 13 are shown in Table 10: Table 10 No. Matrix Br / kGs Br / kGs after diffusion Matrix Hcj / kOe Hcj / kOe after diffusion 12 14.38 14.26 17.5 25.1 13 14.37 14.25 17.5 25.3 In this embodiment, the ratio of the thickness of different regions of the magnets of Experiment No. 12 and Experiment No. 13 is the same, but the thickness of the magnet of Experiment No. 12 along the orientation direction is 12 mm, while the thickness of the magnet of Experiment No. 13 along the orientation direction is 8 mm. It can be seen from the results of Tables 9 and 10 that although the thickness of the two experimental magnets along the orientation direction is different, under the same diffusion source weight gain, the performance of the magnets of Experiment No. 12 and Experiment No. 13 after diffusion is basically the same. Therefore, the method for preparing large-size high-performance RTB rare earth permanent magnets provided by the present invention is suitable for magnets with a thickness of ≥10 mm in the orientation direction of the magnet, but the method is also applicable when the thickness of the magnet in the orientation direction is ≤10 mm. In addition, according to experimental and production data, the magnet preparation method provided by the present invention is more suitable for the preparation of magnets with a thickness of 4 mm to 14 mm in the orientation direction of the magnet.

[0092] Embodiment six: According to the ratio of SC-1 in Table 11, raw materials are taken, smelted, and spun to prepare magnet matrix SC sheets, which are recorded as SC-1. SC-1 is used to prepare RTB rare earth magnetic powder F1 by hydrogen crushing and air flow milling. According to the ratio of the components of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC sheets SC-L1. The composition of auxiliary alloy L1 of experiment No.14 is as follows: Tb: 80.0wt.% Al: 15.0wt.% Co: 5.0wt.% The composition of auxiliary alloy L1 of experiment No.15 is as follows: Tb: 85.0wt.% Al: 15.0wt.% SC-1 was mixed with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and rare earth magnetic powder F2 was prepared by hydrogen crushing and air flow milling. The weight of auxiliary alloy SC sheet SC-L1 was 0.8wt.% of the weight of mixed SC sheet SC-2; The magnetic powder F1, magnetic powder F2 and magnetic powder F1 are sequentially filled into the molding die in a layered powder spreading manner. In this embodiment, the pressing direction is perpendicular to the magnetizing direction during molding. Therefore, the magnetic powder is filled according to the following steps: A powder filling partition is placed in the mold, which divides the mold cavity into three parallel sub-cavities. The widths of the three sub-cavities are 3.0 mm, 12.0 mm, and 3.0 mm, respectively. Then, magnetic powder F1, magnetic powder F2, and magnetic powder F1 are filled in the three sub-cavities, respectively. Figure 2 (b) shown.

[0093] Subsequently, the matrix magnet was prepared by orientation molding, isostatic pressing, vacuum sintering and heat treatment. After sintering, the magnet shrank and the thickness of the magnet in the orientation direction was 12 mm. After cleaning the surface of the matrix magnet, the heavy rare earth element RH diffusion source L2 was deposited on the two surfaces of the magnet perpendicular to the orientation direction by PVD, and grain boundary diffusion treatment was performed. The grain boundary diffusion temperature was 910 ° C, the holding time was 25 h, and the vacuum degree was 3 × 10 -3 Pa~3×10 -2 The diffusion source L2 is made by melting and casting a large ingot of raw materials according to the proportion, and then deposited on the magnet surface by PVD. The weight gain of the diffusion source is 0.6wt.% of the mass fraction of the magnet.

[0094] The composition of the grain boundary diffusion source L2 of Experiment No. 14 is as follows: Tb: 80.0wt.% Al: 10.0wt.% Co: 10.0wt.% The composition of the grain boundary diffusion source L2 of Experiment No. 15 is as follows: Tb: 90.0wt.% Al: 10.0wt.% The magnet after grain boundary diffusion is heat treated at a temperature of 510°C for 3.5 hours, and then cooled to below 80°C to obtain the large-size high-performance RTB rare earth permanent magnet. The magnet surface was sandblasted to expose the fresh surface. The magnet composition was tested by ICP, and the oxygen and carbon content of the magnet was tested by oxygen and carbon analyzer. The microstructure and micro-region composition of the magnet were analyzed by SEM and EPMA. The magnetic properties of the magnet were tested by NIM-62000 equipment. The magnet matrix of Experiment No. 14 and Experiment No. 15 did not contain Al and Co. The magnet was processed into a φ10*10 cylinder, and the magnetic loss was tested after magnetization saturation. The magnetic loss test conditions were 200℃*3h, full open circuit test.

[0095] The magnet compositions (mass fraction) of Experiment No. 14 and Experiment No. 15 are shown in Table 11: Table 11 No. Nd Pr B Cu Ga Co Tb Ti Al Fe TRE O(ppm) C(ppm) SC-1 22.81 6.98 0.92 0.22 0.11 0 0.13 0.12 0 Bal 29.92 / / 14 22.6 6.75 0.92 0.22 0.11 0.8 0.58 0.12 0.18 Bal 29.93 512 358 15 22.7 6.72 0.92 0.22 0.11 0 0.63 0.12 0.18 Bal 30.05 523 410 The magnetic properties and magnetic loss of the magnets after diffusion in Experiment No. 14 and Experiment No. 15 are shown in Table 12: Table 12 No. Br / kGs after diffusion Hcj / kOe after diffusion Magnetic loss% 14 14.17 24.1 0.5 15 14.20 25.2 3.5 In this embodiment, the magnet matrix does not contain Co. The auxiliary alloy and grain boundary diffusion source of the magnet of Experiment No. 14 contain both Al and Co, but the auxiliary alloy and grain boundary diffusion source of the magnet of Experiment No. 15 do not contain Co. It can be seen from Tables 11 and 12 that the remanence of the magnet of Experiment No. 15 after diffusion is the same as that of Experiment No. 14, and the coercive force is higher than that of Experiment No. 14, but the magnetic loss results show that the magnetic loss of Experiment No. 15 is significantly greater than that of Experiment No. 14. The Al element has a lower melting point. When used as an auxiliary alloy and grain boundary diffusion source, it can increase the diffusion depth of the RH element and increase the coercive force of the magnet. However, the temperature coefficient of the Al element is negative, which will reduce the high-temperature magnetic properties of the magnet and increase the magnetic loss of the magnet. Although the Co element will not increase the coercive force of the magnet, it will improve the temperature coefficient of the magnet and reduce the remanence loss of the magnet at high temperature. Therefore, in the present invention, when the magnet M2 element contains Al, a certain amount of Co needs to be added to improve the high-temperature magnetic properties of the magnet.

Claims

1. A large-size, high-performance RTB rare earth permanent magnet, characterized in that The magnet contains the following components in mass fractions: R: 28.5~31.0wt.%, R includes R1 and RH, RH accounts for 0.1~3.0wt.% of the mass fraction of the magnet, RH is at least one of Dy and Tb; the balance of R is R1, R1 includes at least one of Nd, Pr, Ho, Gd, Er, Y, La, Ce; RH accounting for 0.1~1.0% of the mass fraction of the magnet is prepared by grain boundary diffusion; M1: 0.1~1.0wt.%, M1 is one or more of Zn, W, Mo, V, Mn, Zr, Ti, Nb; M2: 0.1~3.0wt.%, M2 is one or more of Cu, Ga, Al; M2, which accounts for 0.01-1% of the mass fraction of the magnet, is obtained by grain boundary diffusion; B: 0.85~1.1wt.%; The balance is T and other unavoidable impurities, T is Fe or Fe and Co; The thickness of the magnet in the orientation direction is 4 mm to 14 mm; the remanence Br of the large-size high-performance magnet is ≥14.0 kGs, and the coercive force Hcj is ≥23.0 kOe.

2. The large-size, high-performance RTB rare earth permanent magnet according to claim 1, characterized in that The magnet is divided into three regions, region A, region B and region A, in the orientation direction, and the thickness X1 of the magnet region A and the thickness X2 of the region B satisfy the following relationship: X2= (1-15)X1; the three regions A, region B and region A all contain 2:14:1 main phase particles with heavy rare earth element RH shells, and the number of 2:14:1 main phase grains with heavy rare earth element RH shells in region A accounts for no less than 40% of the total main phase grains in region A; The magnet has a distance of 20 μm from the outer surface of region A to the interface between region A and region B of the magnet. As the unit distance from the outer surface of region A increases, the average concentration of the heavy rare earth element RH decreases. In the magnet within the region B, with a distance of 20 μm as a basic unit distance, as the distance from the interface between the region A and the region B increases, the difference in average RH element concentration between each basic unit distance is less than 0.1%.

3. The large-size, high-performance RTB rare earth permanent magnet according to claim 1, characterized in that The average content of heavy rare earth RH elements in region A is higher than the average content of heavy rare earth RH elements in region B of the magnet.

4. The large-size, high-performance RTB rare earth permanent magnet according to claim 1, characterized in that The total content of oxygen and carbon elements in the magnet is less than 1000 ppm.

5. The large-size, high-performance RTB rare earth permanent magnet according to claim 1, characterized in that When M2 contains Al, the content of Al in the magnet is ≤0.3wt.%; and T contains Fe and Co; Alternatively, M2 is one or both of Cu and Ga.

6. The large-size, high-performance RTB rare earth permanent magnet according to any one of claims 1 to 5, characterized in that The large-size, high-performance RTB rare earth permanent magnet is prepared according to the following steps: S1: Take raw materials according to the composition ratio, melt and spin to prepare two SC sheets, denoted as SC-1 and SC-3; SC-1 and SC-3 are respectively prepared by hydrogen crushing and air flow milling to prepare RTB rare earth magnetic powders F1 and F3; According to the composition ratio of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC flakes SC-L1, and auxiliary alloy L1 powder is prepared by hydrogen crushing and air flow milling; S2: Prepare rare earth magnetic powder F2 in one of the following two ways: (a) mixing one of SC-1 and SC-3 with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and preparing rare earth magnetic powder F2 by hydrogen crushing and air flow milling, wherein the weight of the auxiliary alloy SC sheet SC-L1 is 0.1wt.%~10.0wt.% of the weight of the mixed SC sheet SC-2; (b) mixing one of the magnetic powders F1 or F3 with the auxiliary alloy L1 powder to obtain rare earth magnetic powder F2; the mixing ratio of the auxiliary alloy L1 powder in the magnetic powder F2 is 0.1wt.%~10.0wt.% of the mass of the magnetic powder F2; S3: filling the magnetic powder F1, magnetic powder F2 and magnetic powder F3 into the forming mold in turn by layered powder spreading; S4: The magnet matrix is ​​prepared by means of orientation molding, isostatic pressing, vacuum sintering and heat treatment; S5: Clean the surface of the magnet substrate obtained in step S4, deposit a diffusion source L2 containing heavy rare earth element RH on two surfaces of the magnet substrate perpendicular to the orientation direction, and perform grain boundary diffusion treatment; the temperature of grain boundary diffusion is 850-1000°C, the holding time is 6-30h, and the vacuum degree is 9×10 -4 Pa~100Pa; after cooling and tempering, the large-size high-performance RTB rare earth permanent magnet is obtained; SC-1 and SC-3 each independently include the following components in mass fractions: R: 28.8~31.3wt.%, R includes R1 and RH, RH accounts for less than 2.9wt.% of the mass fraction of the magnet, RH may be absent, RH is at least one of Dy and Tb; the remainder of R is R1, R1 includes at least one of Nd, Pr, Ho, Gd, Er, Y, La, Ce; M1: 0.1~1.0wt.%, M1 is one or more of Zn, W, Mo, V, Mn, Zr, Ti, Nb; M2: 0.01~2.99wt.%, M2 is one or more of Cu, Ga, Al; B: 0.85~1.1wt.%; The balance is T and other unavoidable impurities, T is Fe or Fe and Co; When M2 contains Al, the content of Al element is ≤0.3wt.%; and T contains Fe and Co; The auxiliary alloy L1 and the diffusion source L2 each independently include the following components in mass fraction: RHL: 70.0~99.5wt.% M2L: 0.05~30.0wt.%, RHL is at least one of Dy and Tb; M2L is one or more of Cu, Ga, Al, and Co.

7. The method for preparing a large-size, high-performance RTB rare earth permanent magnet according to any one of claims 1 to 5, characterized in that The method comprises the following steps: S1: Take raw materials according to the composition ratio, melt and spin to prepare two SC sheets, denoted as SC-1 and SC-3; SC-1 and SC-3 are respectively prepared by hydrogen crushing and air flow milling to prepare RTB rare earth magnetic powders F1 and F3; According to the composition ratio of auxiliary alloy L1, raw materials are taken, smelted, and spun to prepare auxiliary alloy SC flakes SC-L1, and auxiliary alloy L1 powder is prepared by hydrogen crushing and air flow milling; S2: Prepare rare earth magnetic powder F2 in one of the following two ways: (a) mixing one of SC-1 and SC-3 with auxiliary alloy SC sheet SC-L1 to obtain mixed SC sheet SC-2, and preparing rare earth magnetic powder F2 by hydrogen crushing and air flow milling, wherein the weight of the auxiliary alloy SC sheet SC-L1 is 0.1wt.%~10.0wt.% of the weight of the mixed SC sheet SC-2; (b) mixing one of the magnetic powders F1 or F3 with the auxiliary alloy L1 powder to obtain rare earth magnetic powder F2; the mixing ratio of the auxiliary alloy L1 powder in the magnetic powder F2 is 0.1wt.%~10.0wt.% of the mass of the magnetic powder F2; S3: filling the magnetic powder F1, magnetic powder F2 and magnetic powder F3 into the forming mold in turn by layered powder spreading; S4: The magnet matrix is ​​prepared by means of orientation molding, isostatic pressing, vacuum sintering and heat treatment; S5: Clean the surface of the magnet substrate obtained in step S4, deposit a diffusion source L2 containing heavy rare earth element RH on two surfaces of the magnet substrate perpendicular to the orientation direction, and perform grain boundary diffusion treatment; the temperature of grain boundary diffusion is 850-1000°C, the holding time is 6-30h, and the vacuum degree is 9×10 -4 Pa~100Pa; after cooling and tempering, the large-size high-performance RTB rare earth permanent magnet is obtained; SC-1 and SC-3 each independently include the following components in mass fractions: R: 28.8~31.3wt.%, R includes R1 and RH, RH accounts for less than 2.9wt.% of the mass fraction of the magnet, RH may be absent, RH is at least one of Dy and Tb; the remainder of R is R1, R1 includes at least one of Nd, Pr, Ho, Gd, Er, Y, La, Ce; M1: 0.1~1.0wt.%, M1 is one or more of Zn, W, Mo, V, Mn, Zr, Ti, Nb; M2: 0.01~2.99wt.%, M2 is one or more of Cu, Ga, Al; B: 0.85~1.1wt.%; The balance is T and other unavoidable impurities, T is Fe or Fe and Co; When M2 contains Al, the content of Al element is ≤0.3wt.%; and T contains Fe and Co; The auxiliary alloy L1 and the diffusion source L2 each independently include the following components in mass fraction: RHL: 70.0~99.5wt.% M2L: 0.05~30.0wt.%, RHL is at least one of Dy and Tb; M2L is one or more of Cu, Ga, Al, and Co.

8. The method according to claim 7, characterized in that In the step S1, the composition ratio of SC-1 and SC-3 is the same, the composition of magnetic powder F1 and magnetic powder F3 is the same, and the surface area average particle size SMD of magnetic powder F1 and magnetic powder F3 is the same; The Al content in the magnetic powders F1, F2 and F3 is less than 0.3wt.%, or does not contain Al; The auxiliary alloy L1 and the diffusion source L2 have the same composition; in the auxiliary alloy L1 or the diffusion source L2, when M2L contains Al, it must also contain Co.

9. The method according to claim 7, characterized in that In step S3, the method of layering the powder is one of the following: (a) When the pressing direction is parallel to the magnetizing direction: the molding is performed using a molding die with a lower punch that can be raised and lowered. The lower punch of the mold is first adjusted downward by a certain distance A, and then the magnetic powder F1 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance B, and then the magnetic powder F2 is evenly filled; after the powder is scraped flat, the lower punch is further adjusted downward by a certain distance C, and then the magnetic powder F3 is evenly filled. After the powder is scraped flat, orientation molding is performed; the thickness B of the F2 magnetic powder is 1 to 15 times the thickness A or C of the F1 or F3 magnetic powder; (b) When the pressing direction is perpendicular to the magnetizing direction: the magnetic powder is filled in a partitioned manner perpendicular to the magnetizing direction. A powder filling partition is placed in the mold, and the partition divides the mold cavity into three parallel sub-cavities; the widths of the three sub-cavities are A, B and C respectively, the middle sub-cavity is filled with magnetic powder F2, and the two side sub-cavities are filled with magnetic powders F1 and F3, and then orientation molding is carried out; the width B is 1 to 15 times the width A or C.

10. The method according to claim 7, characterized in that In step S5, the diffusion source L2 is prepared by one of the following methods and deposited onto the surface of the magnet substrate: B1: melting and casting a large ingot of the raw materials of the diffusion source L2 with a specific ratio, and depositing it on the surface of the magnet substrate by PVD; B2: The raw materials of the diffusion source L2 with a specific ratio are melted, spun and prepared into alloy powder, which is then deposited on the surface of the magnet substrate by powder coating, spraying, printing and the like.

Citation Information

Cited By

  • Performance-partitioned permanent magnet and preparation method and application thereof

    CN121281959A

  • Performance partitioned permanent magnet and preparation method and application thereof

    CN121281959B